The Combined Use of Pediococcus pentosaceus and Fructooligosaccharide Improves Growth Performance, Immune Response, and Resistance of Whiteleg Shrimp Litopenaeus vannamei Against Vibrio parahaemolyticus - Hong, Nguyen Thi Xuan; Linh, Nguyen Thi Hue; Baruah, Kartik; Thuy, Do Thi Bich; Phuoc, Nguyen Ngoc (Frontiers in Microbiology, 2022)
In this study, we evaluated the effect of probiotic bacteria Pediococcus pentosaceus supplemented at different inclusion levels in a control diet [basal diet containing 0.5% fructooligosaccharide (FOS)] on the growth performance, feed conversion ratio, immune response, and the disease resistance of whiteleg shrimp Litopenaeus vannamei juveniles against Vibrio parahaemolyticus. A control diet with 0.5% FOS but without P. pentosaceus supplementation (Control) was prepared. In addition, three other test diets were also formulated: control diet supplemented with P. pentosaceus at (i) 1 × 106 cfu g–1 diet (P1), (ii) 1 × 107 cfu g–1 diet (P2), or (iii) 1 × 108 cfu g–1 diet (P3). After a 60-day feeding trial, the experimental shrimps were challenged with V. parahaemolyticus. The results showed that dietary supplementation of P. pentosaceus significantly improved the growth performance and immune responses of L. vannamei juveniles. The juveniles that were fed with a P2 or P3 diet recorded the maximum increase in the final body weight, final length, weight gain, and survival rate. The total hemocyte counts, phenoloxidase, and lysozyme activity of shrimp fed with either of these two diets were significantly enhanced. The results also showed that juveniles fed with a P2 or P3 diet exhibited significantly lower mortality when challenged with V. parahaemolyticus. Overall results suggested that a combination of P. pentosaceus at the inclusion level of 1 × 107 cfu g–1 diet (P2) and 0.5% FOS could be considered as a potential synbiotic formulation for improving the growth, health, and robustness of L. vannamei.